1987
DOI: 10.2307/1961958
|View full text |Cite
|
Sign up to set email alerts
|

Elite Ideology and Risk Perception in Nuclear Energy Policy

Abstract: Changing U.S. attitudes toward new technologies are examined, as are explanations of such changes. We hypothesize that increased concern with the risks of new technologies by certain elite groups is partly a surrogate for underlying ideological criticisms of U.S. society. The question of risk is examined within the framework of the debate over nuclear energy. Studies of various leadership groups are used to demonstrate the ideological component of risk assessment. Studies of scientists' and journalists' attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(77 citation statements)
references
References 24 publications
3
71
1
1
Order By: Relevance
“…governments' pro-nuclear positions are in line with previous scholarship that suggests that both political elites and the general public who hold right-of-centre views take a more pronuclear energy stance (Kuklinski et al 1982;Rothman and Lichter 1987;Plutzer et al 1998).…”
Section: The Dynamics Of Public Debate and Mobilisation On Nuclear Ensupporting
confidence: 83%
“…governments' pro-nuclear positions are in line with previous scholarship that suggests that both political elites and the general public who hold right-of-centre views take a more pronuclear energy stance (Kuklinski et al 1982;Rothman and Lichter 1987;Plutzer et al 1998).…”
Section: The Dynamics Of Public Debate and Mobilisation On Nuclear Ensupporting
confidence: 83%
“…Issues that have a bearing on deeply held societal norms and consequential public policies might become entangled with preferences about the role of government in society. The assertion that the climate is changing as a result of human activities, and that addressing it will require a substantial intervention by governments into the otherwise private affairs of individuals and businesses, will have a substantial ideological valence (Rothman and Lichter 1987;Douglas and Wildavsky 1982;Leiserowitz 2005). A large body of research has confirmed that political ideology plays a substantial role in shaping perceptions of climate change, with conservatives (and, more recently, the ''Tea Party'') tending to perceive climate to be stable and benign, and therefore requiring little or no government intervention (Leiserowitz et al 2011;McCright and Dunlap 2011;Weber and Stern 2011;Krosnick et al 2006;Dietz et al 2007;Dunlap and McCright 2008).…”
Section: Perceptions Of Local Weathermentioning
confidence: 99%
“…Some claim that scientists are immune from ideological bias and that risk assessments merely reflect a dispassionate distillation of current scientific knowledge (Rothman, 1994;Rothman & Lichter, 1987). However, the longstanding consensus is that both scientific elites and issue publics (e.g., journalists) show greater evidence of ideological thinking than samples of the mass public (e.g., Converse, 1964;Feldman, 1989;McAllister, 1991).…”
Section: Culture and Worldviewsmentioning
confidence: 99%